The effect of experimentally-induced diabetes on rat hippocampus and the potential neuroprotective effect of Cerebrolysin combined with insulin. A histological and immunohistochemical study. Issue 1 (31st December 2023) - El-Adli, Doaa; Gawish, Salwa A.; AbdElFattah, Amany AbdElFattah Mohamed; Soliman, Mona Fm.
ABSTRACT: Diabetes Mellitus is the most common metabolic disorder affecting central nervous system (CNS) and is associated with altered brain structure. In this study, we assessed the ability of Cerebrolysin, alone and combined with insulin, to protect from the hippocampal degenerative changes in a diabetic rat model. Sixty adult male albino rats were equally divided into: control (gpI), diabetic (gpII), insulin-treated (gpIII), Cerebrolysin-treated (gpIV) and combined Insulin & Cerebrolysin-treated groups (gpV). Type-1 DM was induced by a single intraperitoneal injection of Streptozotocin (65 mg/kg) in groups (II, III, IV & V). Insulin was given subcutaneously (1 U/100g) daily, starting from the 4th day till the end of the experiment. Cerebrolysin was given intraperitonealy (5 ml/kg/day), starting from the 4th day till the end of the experiment. Hippocampus samples were collected 8-weeks post-injection. Hematoxylin & Eosin (H&E) and Immunohistochemical stains were used to assess the degenerative changes. The rat hippocampal region (CA3) and the dentate gyrus (DG) were subjected to microscopic examination and morphometric analysis. The hippocampus of rats of group II showed evident degenerative changes. Changes in immunohistochemical expression of Bax, TNF-alpha, Synaptophysin & GFAP were also detected. The morphometric study revealed changes in the thickness of layers and number of cells. Groups III and IV showed mild improvement in most parameters. Group V demonstrated marked improvement in most parameters and the hippocampus appeared more or less similar to the control. Cerebrolysin is a neurotropic drug that protects from the diabetic degenerative changes, especially if combined with insulin.